Pengaruh Penggunaan Metode Pembelajaran Berbasis Al-Qur’an dan Metode Mustaqilly terhadap Peningkatan Motivasi Belajar Bahasa Arab Siswa di Sekolah Dasar Islam - Effendi, Hasbi Maulana; Rahmadani, Anisa; Ardiansyah, Ridho Frenky (EL-EMIR Institute, 2025)
This study aims to analyze the effect of using the Qur'an-based learning method and the Mustaqilly method on increasing students' motivation to learn Arabic in Islamic schools. High learning motivation is an important factor in learning Arabic, especially in the context of Islamic education, where Arabic has a fundamental role. The Qur'an-based learning method aims to integrate Islamic values ​​and contextual approaches, so that students can relate Arabic learning to their religious understanding. Meanwhile, the Mustaqilly method emphasizes independence and gradual learning, which is designed to help students develop language skills independently and continuously. This study uses a quantitative method with a quasi-experimental design. The research sample was students at an Islamic school in Jakarta, which were divided into two groups: an experimental group using the Qur'an-based and Mustaqilly methods, and a control group using the conventional method. The research instrument was a questionnaire on Arabic learning motivation, which was measured before and after the application of the method to both groups. The results showed that there was a significant increase in Arabic learning motivation in the experimental group compared to the control group. These findings indicate that the Qur'an-based method and the Mustaqilly method can effectively increase students' motivation in learning Arabic. The application of this method not only provides practical language understanding but also increases students' appreciation of Arabic as a religious language. The implication of this study is the importance of a learning approach that integrates spiritual values ​​and independence to increase students' motivation to learn Arabic in Islamic schools.